Pre-service Mathematics Teachers' Concepts Regarding the Professional Competencies Involved in the Teaching of Statistics - Miguel Friz Carrillo; Susan Sanhueza Henríquez (Universidad Autónoma de Baja California, 2011)
In this study, we designed an instrument with a series of competences that had to be evaluated by student teachers enrolled in a course in Statistics Education at a public university in Chile (N=81). The questionnaire was administered at the beginning and end of the program in order to assess and compare the students' a) reflection on practice in a collaborative learning environment, b) the competencies relating to the design of learning tasks, and c) the use of educational technology. The results show that the assessment initially made by students is determined by what they already know about statistics (intuitive knowledge. However, their concepts of professional skills related to the nature of statistics (mathematical competency), and their pedagogical knowledge needed for teaching and learning of statistics in secondary education (professional competency), undergo positive modification as the course goes on.